The Role of Students in Controlling the “Klitih” Phenomenon in the Special Region of Yogyakarta, Indonesia - Aldi Rizki Padila; Anis Mufida; Syahrani Nur Azizah; Rahmi Rahmi; Luki Wijayanti (Haluan Sastra Budaya, 2024)
The Klitih phenomenon, common in the Special Region of Yogyakarta, Indonesia, is characterized by disruptive nighttime activities of teenagers that cause harm to the community, intentionally or unintentionally. The conduct of these teenagers is garnering significant attention on social media platforms, with numerous articles addressing the klitih phenomenon, even though little effective control over it exists presently. More than 300 articles exploring this phenomenon were found on Google Scholar. This paper aims to explore the klitih phenomenon with a specific focus on the role of students. A qualitative research approach was employed, involving a review of existing literature and conducting case studies that included interviews with eight participants, including students, professors, and members of the community. Descriptive and bibliometric analyses were utilized to examine their responses. The interviews were undertaken to gather data that might contribute to policy formulation and offer recommendations concerning the klitih phenomenon. The discussion primarily zeroes in on the role of students in mitigating klitih behaviors through providing counseling and socialization for affected families in the region. The study suggests that tackling the underlying family issues could be a key strategy in preventing the klitih phenomenon. Furthermore, it recommends that students can also contribute to managing the klitih phenomenon, which is vital for the healthy development of adolescents, particularly in terms of their interpersonal behaviors.